(untitled) (International Journal of Engineering and Computer Science, 2015)
The amount of information accumulated in the internet is massive. The information is searched in the internet using a search engine. The current search engines searches for the needed information based on the keywords which the users have typed. These search and retrieval are based on syntactic analysis of keyword instead of contextual analysis. In order to overcome this issue, the need of Semantic Search Engines is increasing. The Semantic Web is an extension of the current web in which Information retrieval is based on the contextual analysis of user search query which is a more meaningful search. In this paper we identify the different approaches and techniques used in different search engines as well as the analysis and comparison of various semantic web search engines based on various parameter to find out their features and limitations. Based on these analyses of different search engines, a comparative study is done to identify relative strengths in semantic web search engines.